Effect of heat-killed Streptococcus thermophilus on type 2 diabetes rats - Xiangyang Gao; Fei Wang; Peng Zhao; Rong Zhang; Qiang Zeng (PeerJ, 2019)
Background and Aims The link between gut microbiota and type 2 diabetes (T2D) has been addressed by numerous studies. Streptococcus thermophilus from fermented milk products, has been used as a probiotic in previous research. However, whether heat-killed S. thermophilus can improve the glycemic parameters of diabetic rats remains unanswered. In this study, we evaluated the effect of heat-killed S. thermophilus on T2D model rats and the potential mechanisms of the effect. Methods Zucker diabetic fatty (ZDF) rats were used to generate a diabetic rat model induced by feeding a high-fat diet. Heat-killed S. thermophilus were orally administered to normal and diabetic rats for 12 weeks. Intestinal microbiota analysis, histology analysis, oral glucose tolerance test and measurement of inflammatory factors were performed. Results We found that heat-killed S. thermophilus treatment reduced fasting blood glucose levels and alleviated glucose intolerance and total cholesterol in diabetic ZDF rats. Additionally, heat-killed S. thermophilus increased the interleukin 10 while reducing the levels of lipopolysaccharide, interleukin 6, and tumor necrosis factor-α in diabetic ZDF rats. The heat-killed S. thermophilus treatment can normalize the structure of the intestinal and colon mucosal layer of diabetic rats. The characteristics of the gut microbiota in heat-killed S. thermophilus-treated and control rats were similar. At the genus level, the abundances of beneficial bacteria, including Ruminococcaceae, Veillonella, Coprococcus, and Bamesiella, were all significantly elevated by heat-killed S. thermophilus treatment in ZDF diabetic rats. Conclusion Our study supports the hypothesis that treatment with heat-killed S. thermophilus could effectively improve glycemic parameters in T2D model rats. In addition, the potential mechanisms underlying the protection maybe include changing the composition of gut microbiota, reinforcing the intestinal epithelial barrier and the immunity of the intestinal mucosa, decreasing the level of inflammation, and then reducing the insulin resistance.